As time goes by ... maintaining longitudinal satisfaction: a perspective of hedonic adaptation. Issue 1 (8th February 2016) - Ying, Yu; Jing, Fengjie; Nguyen, Bang; Chen, Junsong
Abstract : Purpose: The purpose of this paper is to improve our understanding of how firms can maintain longitudinal satisfaction. Previous research on longitudinal satisfaction demonstrates that the product attributes weight on satisfaction shifts over time. However, the existing literature lacks an understanding of the intervening mechanism. Inspired by the hedonic adaptation theory, this research first argues that the shift depends on the attribute's variability. Then, it posits that hedonic adaptation might play a mediation role in connecting the attribute's weight and longitudinal satisfaction. Finally, the research incorporates consumer intentional activities into the antecedents of longitudinal satisfaction. Design/methodology/approach: The authors test a series of hypotheses across two studies. Using the Slope-shift Parameter Theory and Structural Equation Modeling, data collected from smartphone owners in four MBA classes (Study 1) and eight business venues in China (Study 2) are analyzed to confirm the research model. Findings: The findings suggest that hedonic adaptation occurs during the ownership process. It is revealed that both the attribute's variability and consumption behavior play important roles in sustaining long-term satisfaction, confirming the mediating effects of hedonic adaptation on the relationship above. Originality/value: The hedonic adaptation theory is applied to study the mediating role of product attribute variability and consumption behavior in sustaining customer satisfaction over time. Three contributions are offered: First, hedonic adaptation occurs during the ownership process; second, the attribute's variability and consumption behavior both play important roles in sustaining longitudinal satisfaction; third, the mediating effects of hedonic adaptation are confirmed for the relationship between attribute's variability and sustaining satisfaction and consumption behavior and sustaining satisfaction.